2023
DOI: 10.1007/s40894-022-00203-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Qualitative Research Focusing on Emotional Distress Among Adolescents: Perceived Cause and Help-Seeking

Abstract: Causal attributions and help-seeking is not well explored among adolescents, despite evidence of perceived causes for difficulties influencing how adults engage with treatment and seek help. This study reviewed extant literature to understand what adolescents at increased risk of developing mental health difficulties and those with clinically significant symptoms perceive to be the cause of emotional distress; to determine the extent to which perceived cause influences help-seeking; and to identify potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In exploring further the role of perceived cause for emotional distress in relation to help-seeking among adolescents, this work broadly supports our earlier systematic review of the literature ( 63 ) where four themes related to causal attribution and help seeking were identified, including: (1) cause and implications for self-preservation; (2) the degree of personal and wider knowledge and understanding of cause; (3) perceived extent of control in managing cause; and (4) cause having potential to affect others. However, findings from O'Neill et al ( 63 ) were drawn from literature that did not explicitly focus on causal attributions for emotional distress and subsequent approach to help-seeking. To narrow this gap, the present study offered this explicit focus by drawing comparisons with our companion study ( 5 ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In exploring further the role of perceived cause for emotional distress in relation to help-seeking among adolescents, this work broadly supports our earlier systematic review of the literature ( 63 ) where four themes related to causal attribution and help seeking were identified, including: (1) cause and implications for self-preservation; (2) the degree of personal and wider knowledge and understanding of cause; (3) perceived extent of control in managing cause; and (4) cause having potential to affect others. However, findings from O'Neill et al ( 63 ) were drawn from literature that did not explicitly focus on causal attributions for emotional distress and subsequent approach to help-seeking. To narrow this gap, the present study offered this explicit focus by drawing comparisons with our companion study ( 5 ).…”
Section: Discussionsupporting
confidence: 77%
“…There may also be a desire not to burden others with their difficulties ( 71 ). In our systematic literature review ( 63 ), we too found that the degree to which the perceived cause had implications for self-preservation or impacting others influenced help-seeking, although cause having the potential to impact others was only found as a theme for the at-risk group in our review and not the clinical group ( 63 ). The present study empirically demonstrates this association once again within an at-risk group.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The DSM-5 is based on symptom criteria that largely discounts etiology and the subjective understanding of why one is depressed, which likely contributes to its low diagnostic validity for depressive disorders in this age-group ( 14 17 ). A shared understanding of the causes and contributing factors is essential for therapeutic alliance, and subjective causal beliefs seem to influence help-seeking ( 18 ). An integrated individual understanding also affects compliance with treatment and ability to handle symptoms ( 19 ).…”
Section: Introductionmentioning
confidence: 99%